Mentoring and Retaining a Diverse Workforce
CSUCI has aimed to promote diversity, equity, inclusion, and accessibility through our recruitment, hiring, and retention practices for faculty, staff, and administrators, includingsenior leadership. A first step towards enhancing awareness and promoting diverse perspectives campus-wide has been to require DEIA-related courses of all CSUCI employees, includingDiscrimination, Harassment, and Retaliation Prevention Program for Supervisors, Discrimination, Harassment, and Retaliation Prevention Program for Non-Supervisors, andGender Equity & Title IX. In Fall 2022, all employees were invited to join a Critical Learning Collective (IEAP 4.2) for the purpose of studying campus climate data and makingrecommendations for improvement. Many of these recommendations focused on ensuring our continued emphasis and accountability for advancing racial and social justice. While not specifically advertised as a mentoring or retention effort, participant survey data indicate that these groups functioned strongly in this purpose.